The Canonization of St Francis Xavier in Spanish Habsburg Lands: A Poetry Challenge in Madrid, Sacristy Paintings by André Reinoso in Lisbon and an Altarpiece by Pieter Pawel Rubens in Antwerp - Jean Andrews (Religions, 2023)
This article examines Jesuit representation of the exploits of Francis Xavier, ‘the Apostle of the East’, in celebration of his canonization in 1622 and in the Jesuit campaign to have him canonized prior to that. Pageants in Madrid, Lisbon and Antwerp are examined, along with prior pictorial depictions of Francis’ miracles and activities, taking into account the gulf between the political realities of proselytization in the Portuguese territories of influence in the East and the hagiography of 1622. The work of Rubens, the Portuguese painter André Reinoso and three Spanish Golden Age poet/playwrights are analyzed, exploring variance in the application of a universal Jesuit aesthetic founded on the melding of the Classical and the Catholic in response to the local conditions for which each ephemeral event and work of art were produced.